Molecular Characterization of Schizophrenia Viewed by Microarray Analysis of Gene Expression in Prefrontal Cortex - Mirnics, Károly; Middleton, Frank A.; Marquez, Adriana; Lewis, David A.; Levitt, Pat (Neuron (Cambridge, Mass.), 2000)
Microarray expression profiling of prefrontal cortex from matched pairs of schizophrenic and control subjects and hierarchical data analysis revealed that transcripts encoding proteins involved in the regulation of presynaptic function ( PSYN) were decreased in all subjects with schizophrenia. Genes of the PSYN group showed a different combination of decreased expression across subjects. Over 250 other gene groups did not show altered expression. Selected PSYN microarray observations were verified by in situ hybridization. Two of the most consistently changed transcripts in the PSYN functional gene group, N-ethylmaleimide sensitive factor and synapsin II, were decreased in ten of ten and nine of ten subjects with schizophrenia, respectively. The combined data suggest that subjects with schizophrenia share a common abnormality in presynaptic function. We set forth a predictive, testable model.